THE APPLICATION OF A MULTIMEDIA-ASSISTED PROBLEM-BASED LEARNING MODEL BASED ON ANDROID TO ENHANCE STUDENTS' CRITICAL THINKING SKILLS - Amiruddin Amiruddin; Endang Surahman; Chaerul Rochman (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2024)
The study’s goals are to find out how the students in class IX-A at MTsN 11 Tasikmalaya’s critical thinking skills and activities improved after using the problem-based learning (PBL) model with the help of multimedia apps on their Android phones and to see how they felt about the model. We conducted this classroom action research in three cycles, utilizing the Kurt Lewin design, which included stages of planning, implementation, observation, and reflection. Multiple-choice tests with reasons were used to measure critical thinking skills, while student activity sheets and questionnaires were used to assess student activity and responses. The results showed an increase in student activity, from 60.2% (poor) in cycle I to 78.5% (good) in cycle II and 80.6% (good) in cycle III. An increase in critical thinking skills also occurred, with an N-Gain value of 0.43 (low) in cycle I, increasing to 0.68 (moderate) in cycle II and 0.69 (moderate) in cycle III. There was no significant difference between male and female students. In general, the students’ response to the Android-based multimedia-assisted PBL model was positive, with a score of 80.1%.